GAMBARAN PENGETAHUAN GIZI IBU HAMIL TRIMESTER PERTAMA DAN POLA MAKAN DALAM PEMENUHAN GIZI DI WILAYAH KERJA PUSKESMAS PARSOBURAN KECAMATAN HABINSARAN KABUPATEN TOBA SAMOSIR TAHUN 2013 - Helena Sipahutar; Evawany Y Aritonang; Muhammad Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Nutrient is one of main determinant factors for the quality of human resources. The needs of food can be seen not only from its portion, but also from the quality of nutrient substances found in the food consumed. The fulfillment of nutrient substance for pregnant mother are influenced by some factors and one of the factors is knowledge of the mother. This research was intended to know the knowledge of pregnant mother of first trisemester about nutrient and eating pattern for the fulfillment of nutrient. This research used descriptive design and sampling techniques used total sampling. Data collection was carried out in September 2013 using questionnaire consisting of 2 parts, namely first part contained the demography data and second part contained the questionnaire about the knwoledge of the pregnant mother of first trisemester in the fulfillment of nutrient. The data on eating pattern was taken from the interview using food recall, then analyzed using frequency distribution table and the total respondents was for 54. The results of research showed that mostly the knowledge of respondents were with medium knowledge for 24 respondents (44.4%), and the least were with good knowledge for 14 respondents (25.9%). Energy intake less of 38.9% with moderate knowledge , whereas good knowledge of 3.7% with good energy intake. Protein intake less of 22.2% with moderate knowledge, whereas good knowledge of 1.9% with sufficient protein intake. Based on the reuslts of research, need for increased knowledgeand information to the first trimesterpregnant women about the importanceof a diet that is nutritious and balanced and as preparation for yourself during pregnancy or after childbirth. Key words : Knowledge of nutrition, food pattern, nutritiont fulfillment, first trismester of pregnant women